MODEL PREDICT OBSERVE EXPLAIN UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM DI KELAS IV SEKOLAH DASAR - Ambyah Harjanto; Mareyke Jessy Tanod (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2018)
This research is motivated by the low understanding of concepts in learning the science of alma. This study aims to improve concept understanding in grade IV of SD Negeri 1 Durian Payung Bandar Lampung by using the learning model predict observe explain. The research method used by the researcher is a classroom action research, with a total of 20 students. This research took place in 2 cycles, each cycle consisting of 2 actions. The techniques used in data collection are observation, tests, interviews, documentation, and field notes. The results showed that the application of the learning model predict observe explain can improve understanding of concepts in natural science learning in Class IV of Durian Payung Elementary School, Bandar Lampung.